Topological magnetic order and superconductivity in EuRbFe4As4 - Hemmida, M.; Winterhalter-Stocker, N.; Ehlers, D.; Von Nidda, H-A Krug; Yao, M.; Bannies, J.; Rienks, E. D. L.; Kurleto, Rafał; Felser, Claudia; Buechner, B.; Fink, J.; Gorol, S.; et al. (Physical Review B, 2021)
We study single crystals of the magnetic superconductor EuRbFe4As4 by magnetization, electron spin resonance (ESR), angle-resolved photoemission spectroscopy, and electrical resistance in pulsed magnetic fields up to 63 T. The superconducting state below 36.5 K is almost isotropic and is only weakly affected by the development of Eu2+ magnetic order at 15 K. On the other hand, for the external magnetic field applied along the c axis the temperature dependence of the ESR linewidth reveals a Berezinskii-Kosterlitz-Thouless topological transition below 15 K. This indicates that Eu2+ planes are a good realization of a two-dimensional XY magnet, which reflects the decoupling of the Eu2+ magnetic moments from superconducting FeAs layers.
CRIS-Team Scopus Importer:2022-04-14